2013
DOI: 10.12968/bjcn.2013.18.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B: raising awareness in the South Asian community in Preston

Abstract: In total 156 participants, all offered HBV testing and HBV vaccinations. 2 HBV surface antigen positive (HBsAg) positives, 10 past infection (HBsAg negative, antiHBC positive), 11 contacts followed up for testing and vaccinations. In conclusion, the initiative endeavours to increase the awareness of HBV amongst the population profile in order to improve the health of the South Asian community in the wider population as a direct result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In our previous study, we discovered HBV infection in 8% of the mentally disabled patients [23]. The present study, which was conducted on nurses caring for the same patients, showed an infection rate of 3%, which indicates a strict control of the HBV prevalence among the staff.…”
Section: Discussionsupporting
confidence: 60%
“…In our previous study, we discovered HBV infection in 8% of the mentally disabled patients [23]. The present study, which was conducted on nurses caring for the same patients, showed an infection rate of 3%, which indicates a strict control of the HBV prevalence among the staff.…”
Section: Discussionsupporting
confidence: 60%
“…London-based polio booster campaign, multiple innovations were seen in the delivery of vaccinations to marginalised groups, including offering incentives and flexible arrangements and infrastructure (e.g. out-of-hours clinics and alternative settings for vaccination (36)(37)(38)(39)(40). How these approaches could be used for delivering routine immunisations to migrants must be considered (41), ensuring the involvement and support of these communities in research and policy decisions.…”
Section: Discussionmentioning
confidence: 99%
“…PHAs also funded faith leaders to build community relationships among immigrant communities [48,106], and further bolster their work with vulnerable populations [107]. As seen in tight-knit faith communities, ethno-racial minorities, and marginalized communities [96,[108][109][110], vaccine confidence among African Americans [72], Korean immigrant church goers [46], minoritized Jewish populations in the United Kingdom [111], and Rohingya refugees in Pakistan [112,113] increased.…”
Section: Plos Global Public Healthmentioning
confidence: 99%